Humoral immune responses in koalas (Phascolarctos cinereus) either naturally infected with Chlamydia pecorum or following administration of a recombinant chlamydial major outer membrane protein vaccine. Issue 6 (3rd February 2016) - Khan, Shahneaz Ali; Polkinghorne, Adam; Waugh, Courtney; Hanger, Jon; Loader, Jo; Beagley, Kenneth; Timms, Peter
Abstract: The development of a vaccine is a key strategy to combat the widespread and debilitating effects of chlamydial infection in koalas. One such vaccine in development uses recombinant chlamydial major outer membrane protein (rMOMP) as an antigen and has shown promising results in several koala trials. Previous chlamydial vaccine studies, primarily in the mouse model, suggest that both cell-mediated and antibody responses will be required for adequate protection. Recently, the important protective role of antibodies has been highlighted. In our current study, we conducted a detailed analysis of the antibody-mediated immune response in koalas that are either (a) naturally-infected, and/or (b) had received an rMOMP vaccine. Firstly, we observed that naturally-infected koalas had very low levels of Chlamydia pecorum -specific neutralising antibodies. A strong correlation between low IgG total titers/neutralising antibody levels, and higher C. pecorum infection load was also observed in these naturally-infected animals. In vaccinated koalas, we showed that the vaccine was able to boost the humoral immune response by inducing strong levels of C. pecorum -specific neutralising antibodies. A detailed characterisation of the MOMP epitope response was also performed in naturally-infected and vaccinated koalas using a PepScan epitope approach. This analysis identified unique sets of MOMP epitope antibodies between naturally-infected non-protected and diseased koalas, versus vaccinated koalas, with the latter group of animals producing a unique set of specific epitope-directed antibodies that we demonstrated were responsible for the in vitro neutralisation activity. Together, these results show the importance of antibodies in chlamydial infection and immunity following vaccination in the koala.